EDUKASI PEMAKAIAN KONTRASEPSI IMPLANT PADA AKSEPTOR KB - Novita Br Ginting Munthe; Iskandar Markus Sembiring; Sri Wulan; Ika Nur Saputri; Rahmad Gurusinga (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Institut Kesehatan Medistra Lubuk Pakam, 2021)
The contraceptive program that is promoted and effective is the long-term contraceptive method (MKJP) with Implant being one of the leading methods. The trend of MKJP Implant achievement rates has decreased in North Sumatra Province from year to year. Increased knowledge through health education related to the use of contraceptive implants in family planning acceptors is one way to achieve reproductive health for women of childbearing age in an effort to control the population. The purpose of this activity is to provide health education that will have a positive impact if mothers participate in these activities properly. Participants in the provision of health education were all family planning acceptors who visited the Bangun Purba Health Center, Bangun Purba District, totaling 28 people. In carrying out the activity, a questionnaire was used to collect participant data based on the level of knowledge about implant contraceptive. The conclusion of this activity is that it is very important for family planning acceptors to educate about the use of implant contraceptives in order to break the controversial issues that are developing in the community regarding the side effects caused by using contraceptives, especially implants.